2021
DOI: 10.1158/1078-0432.ccr-20-3872
|View full text |Cite
|
Sign up to set email alerts
|

Cell Type–specific Adaptive Signaling Responses to KRASG12C Inhibition

Abstract: Purpose: Covalent inhibitors of KRASG12C specifically target tumors driven by this form of mutant KRAS, yet early studies show that bypass signaling drives adaptive resistance. Although several combination strategies have been shown to improve efficacy of KRASG12C inhibitors (KRASi), underlying mechanisms and predictive strategies for patient enrichment are less clear. Experimental Design: We performed mass spectrometry–based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 48 publications
5
67
0
Order By: Relevance
“…However, another study suggests that wild-type RAS activation mediated by multiple RTKs, rather than a single RTK, is responsible for the acquired resistance of KRAS-G12C inhibitors (ARS-1620 and sotorasib) in various types of cancer cell lines [32]. Regardless, many independent studies demonstrate the importance of PTPN11/SHP2 as a common downstream of RTKs to activate the wild-type or mutant KRAS protein in mediating acquired drug resistance [10,[32][33][34][35][36][37]. Clinical trials (NCT04330664) are ongoing to test the combination with TNO155 (SHP2 inhibitor) and adagrasib in patients with advanced solid tumors carrying KRAS-G12C mutation.…”
Section: Resistance To Kras-g12c Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study suggests that wild-type RAS activation mediated by multiple RTKs, rather than a single RTK, is responsible for the acquired resistance of KRAS-G12C inhibitors (ARS-1620 and sotorasib) in various types of cancer cell lines [32]. Regardless, many independent studies demonstrate the importance of PTPN11/SHP2 as a common downstream of RTKs to activate the wild-type or mutant KRAS protein in mediating acquired drug resistance [10,[32][33][34][35][36][37]. Clinical trials (NCT04330664) are ongoing to test the combination with TNO155 (SHP2 inhibitor) and adagrasib in patients with advanced solid tumors carrying KRAS-G12C mutation.…”
Section: Resistance To Kras-g12c Inhibitormentioning
confidence: 99%
“…In addition, the activation of the PI3K-AKT-mTOR pathway contributes to the development of sotorasib resistance in human PDAC cell line in vitro and in xenograft mouse models [38]. Gene set enrichment analysis and mass spectrometry-based phosphoproteomics analysis found that induction of epithelial-to-mesenchymal transition (EMT) promotes resistance to sotorasib or ARS-1620 through activation of PI3K or ERK pathway in NSCLC cells in a cell type-dependent manner [35,39]. Nuclear factor, erythroid 2 like 2 (NFE2L2, best known as NRF2) regulated by kelch like ECH associated protein 1 (KEAP1) is a key transcription factor in cellular antioxidant response.…”
Section: Resistance To Kras-g12c Inhibitormentioning
confidence: 99%
“…Several mechanisms for the reactivation of MAPK signaling, as well as for mutant KRAS-independent activation of PI3K signaling, have been reported [42,60,[62][63][64]. As presented earlier, the inhibition of the MAPK pathway induces feedback reactivation of MAPK signaling via multiple activated RTKs in various types of cancer cell lines.…”
Section: Kras Dependency and Response To Kras G12c Inhibitorsmentioning
confidence: 81%
“…To date, multiple preclinical studies have reported various mechanisms of resistance to KRAS G12C inhibitors. These studies overall suggest the reactivation of MAPK signaling and/or mutant KRAS-independent activation of the PI3K pathway as common modalities to bypass KRAS G12C blockade, ultimately resulting in KRAS G12C inhibitor resistance [42,[62][63][64].…”
Section: Kras Dependency and Response To Kras G12c Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation